2009
DOI: 10.3340/jkns.2009.46.6.545
|View full text |Cite
|
Sign up to set email alerts
|

Sole Stenting Technique for Treatment of Complex Aneurysms

Abstract: Objective : Complex aneurysms such as fusiform and very small aneurysms (< 3 mm) are challenging in neurovascular and endovascular surgery. Author reports follow-up results of 9 cases treated by sole stent technique with pertinent literature review. Methods : A retrospective study was made of 9 patients who were treated by sole stenting technique for cerebral aneurysm between January 2003 and January 2009. Two of them had fusiform aneurysm, 5 had very small aneurysm, and 2 had small saccular aneurysm. Five pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
5
0
4
Order By: Relevance
“…Kim 12 reported on the successful conservative treatment of a patient with suboptimal stent deployment; however, the individual presented with normal blood flow on postoperative angiography. Based on an analysis of 9 cases, Fiorella et al 6 concluded that symptomatic patients with delayed in-stent stenosis should undergo endovascular angioplasty or bypass surgery, whereas a "strategy of watchful waiting may be effective" in the case of asymptomatic subjects.…”
Section: 21mentioning
confidence: 99%
“…Kim 12 reported on the successful conservative treatment of a patient with suboptimal stent deployment; however, the individual presented with normal blood flow on postoperative angiography. Based on an analysis of 9 cases, Fiorella et al 6 concluded that symptomatic patients with delayed in-stent stenosis should undergo endovascular angioplasty or bypass surgery, whereas a "strategy of watchful waiting may be effective" in the case of asymptomatic subjects.…”
Section: 21mentioning
confidence: 99%
“…[1][2][3][4][5] A few case series with the use of the sole stent placement technique in the treatment of complex fusiform MCA aneurysms also exist in the literature. 6,7 Additionally, Y-stent flow diversion by use of self-expandable stents with a closed-cell design without endosaccular coiling has also been reported to be effective in a small, selected case series, including 5 MCA bifurcation aneurysms with complete occlusion in the follow-up. 8 The introduction of the Pipeline Embolization Device (PED) (Covidien/ev3, Irvine, California) as a dedicated flow diverter added a new dimension to this treatment strategy, with its being porous enough to preserve the patency of the branch vessels covered by the construct.…”
mentioning
confidence: 99%
“…45 Sole stenting is a reconstructive method that has been described as an alternative treatment for complex aneurysms. 9,15,46 Utilizing flow diversion in the treatment of complex intracranial aneurysms in the United States is challenging secondary to the current regulatory environment regarding the use of stents specifically designed for flow diversion.…”
Section: Discussionmentioning
confidence: 99%